2023
DOI: 10.1002/advs.202205862
|View full text |Cite|
|
Sign up to set email alerts
|

AQP4 Aggravates Cognitive Impairment in Sepsis‐Associated Encephalopathy through Inhibiting Nav1.6‐Mediated Astrocyte Autophagy

Abstract: The pathology of sepsis‐associated encephalopathy (SAE) is related to astrocyte‐inflammation associated with aquaporin‐4 (AQP4). The aim here is to investigate the effects of AQP4 associated with SAE and reveal its underlying mechanism causing cognitive impairment. The in vivo experimental results reveal that AQP4 in peripheral blood of patients with SAE is up‐regulated, also the cortical and hippocampal tissue of cecal ligation and perforation (CLP) mouse brain has significant rise in AQP4. Furthermore, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Recent studies have shown that AQP4 regulates astrocyte‐mediated neuroinflammation. [ 46 , 47 , 48 ] Consistently, the upregulation of CCI‐induced inflammatory factors ( Tnf, Il6, Il1b ) and astrocyte‐related mediators ( Ccl2 and Cxcl1 ) was reversed by AQP4 inhibition (Figure 4D1–D5 ). Notably, these gene expressions were also reversed by NFAT5 inhibitor administration (Figure S5C1–C5 , Supporting Information), suggesting a link between NFAT5 and AQP4 in the regulation of neuroinflammation.…”
Section: Resultsmentioning
confidence: 56%
“…Recent studies have shown that AQP4 regulates astrocyte‐mediated neuroinflammation. [ 46 , 47 , 48 ] Consistently, the upregulation of CCI‐induced inflammatory factors ( Tnf, Il6, Il1b ) and astrocyte‐related mediators ( Ccl2 and Cxcl1 ) was reversed by AQP4 inhibition (Figure 4D1–D5 ). Notably, these gene expressions were also reversed by NFAT5 inhibitor administration (Figure S5C1–C5 , Supporting Information), suggesting a link between NFAT5 and AQP4 in the regulation of neuroinflammation.…”
Section: Resultsmentioning
confidence: 56%
“… 12 , 14 Astrocytes may also be involved in the neuroinflammation with significant expression of TNF-α and IL-1β. 17 Microglia sorted from the brains of septic mice showed the elevated expression of TNF-α but not IL-1β, suggesting the possible involvement of the proinflammatory actions of macrophages and/or astrocytes.…”
Section: Discussionmentioning
confidence: 96%
“… 15 , 16 It is important to prevent the infiltration of circulating monocytes into the brain parenchyma. Proinflammatory cytokines, such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNF-α), the major sources of which are microglia 12 and also astrocytes, 17 are known to cause BBB breakdown, leading to the infiltration of circulating macrophages. 18 Elevated intracellular cyclic AMP (cAMP) levels have been shown to prevent proinflammatory activation of microglia.…”
Section: Introductionmentioning
confidence: 99%
“…The initial results of these studies demonstrated an upregulation of AQP9 mRNA expression in ARDS patients, although when a validation analysis was performed on a separate group of ARDS patients and healthy individuals, no significant changes in AQP9 expression were detected [ 16 ]. Finally, AQP4 protein levels were found to be elevated in the blood samples of patients suffering from sepsis-associated encephalopathy (SAE) [ 17 ]. Table 1 presents an overview of human studies on the expression of AQPs in the setting of sepsis and related disorders.…”
Section: Aquaporin Expression In Clinical and Experimental Models Of ...mentioning
confidence: 99%
“…In the lung tissue of a CLP-induced sepsis rat model, downregulation of lncRNA-5657 resulted in a reduction in lung inflammation caused by CLP [ 58 ]. Moreover, the elevated AQP4 protein levels found in cortical and hippocampal tissues of CLP-induced SAE mice could be reduced via the downregulation of lncRNA-5657 [ 17 ]. Finally, the neuronal degradation and necrosis found in the hippocampus of CLP sepsis-induced rats were attenuated following lncRNA-5657 silencing [ 63 ].…”
Section: Aquaporin Long Non-coding Rnas and Micro Rnas In Clinical An...mentioning
confidence: 99%